'Un tal Ernestico/a certain Ernestico': On the structure of proper names - José Camacho (Glossa, 2019)
Proper names are usually assumed to be definite. In this paper we question this assumption by analyzing the Spanish construction 'un tal ‘X’' ‘a certain ‘X’’. We show that ‘'un tal ‘X’'’ has two meanings, one evidential and one evaluative, and with the evidential meaning the determiner must be indefinite. In those conditions, ‘X’ is always a proper name. We argue that proper names usually involve a presuppositional, familiar referent, expressed through the definite determiner. However, evidentiality conflicts with familiarity, hence the definite is no longer possible. Finally, we argue that proper names are licensed by features from a hierarchy that applies either to the referential base, yielding person licensing, or to an evidential base, producing sequences such as 'un tal ‘X’'.